Haavelmo Hipotezinin Geçerliliği: Türkiye Örneği(The Validity Of Haavelmo Hypothesis: The Case Of Turkey) - Rahmi YAMAK (Yönetim ve Ekonomi, 2019)
Developing countries which have inadequate domestic savings to finance investments need to use external resources. In this context, it is expected that capital flows to developing countries will enhance the economic growth by closing the investment and technology gaps togetger with national resources. However, it is also known that capital flows will damage the macroeconomical balance by reducing the domestic savings, increasing consumption, increasing the value of real exchange rate and increasing the current account deficit of the receiving country. Foreign capital is a significant part of the development of the world economy, thus the effects of capital inflows on the macroeconomic indicators investageted intensely in the literataure. In this study, the effects of direct and indirect capital inflows on the domestic savings within Haavelmo Hypothesis for Turkey is investigated. Haavelmo argues that domestic savings could be negative if the capital inflows is very large. The data used in the study cover period of 1986-2015. The ARDL bounds test is used to analyze the long-run relationship between capital inflows and domestic savings. The dynamic relations of these two variables are investigated with the Toda-Yamamoto causality test. The results of ARDL bounds test supports the Haavelmo Hypothesis for Turkey. In other words, capital inflows reduce domestic savings. The results of the Toda-Yamamoto causality test shows the existence of bidirectional causality between portfolio investments and domestic savings.